Prefrontal Connectivity and Glutamate Transmission: Relevance to Depression Pathophysiology and Ketamine Treatment - Abdallah, Chadi G.; Averill, Christopher L.; Salas, Ramiro; Averill, Lynnette A.; Baldwin, Philip R.; Krystal, John H.; Mathew, Sanjay J.; Mathalon, Daniel H. (Biological psychiatry : cognitive neuroscience and neuroimaging, 2017)
Prefrontal global brain connectivity with global signal regression (GBCr) was proposed as a robust biomarker of depression and was associated with ketamine’s mechanism of action. Here, we investigated prefrontal GBCr in treatment-resistant depression (TRD) at baseline and following treatment. Then, we conducted a set of pharmacological challenges in healthy subjects to investigate the glutamate neurotransmission correlates of GBCr. In the cohort A study, we used functional magnetic resonance imaging to compare GBCr between 22 patients with TRD and 29 healthy control subjects. Then, we examined the effects of ketamine and midazolam on GBCr in patients with TRD 24 hours posttreatment. In the cohort B study, we acquired repeated functional magnetic resonance imaging in 18 healthy subjects to determine the effects of lamotrigine (a glutamate release inhibitor), ketamine, and lamotrigine-by-ketamine interaction. In the cohort A study, patients with TRD showed significant reduction in dorsomedial and dorsolateral prefrontal GBCr compared with healthy control subjects. In patients with TRD, GBCr in the altered clusters significantly increased 24 hours following ketamine (effect size = 1.0, confidence interval = 0.3 to 1.8) but not following midazolam (effect size = 0.5, confidence interval = −0.6 to 1.3). In the cohort B study, oral lamotrigine reduced GBCr 2 hours postadministration, while ketamine increased medial prefrontal GBCr during infusion. Lamotrigine significantly reduced the ketamine-induced GBCr surge. Exploratory analyses showed elevated ventral prefrontal GBCr in TRD and significant reduction of ventral prefrontal GBCr during ketamine infusion in healthy subjects. This study provides the first replication of the ability of ketamine to normalize depression-related prefrontal dysconnectivity. It also provides indirect evidence that these effects may be triggered by the capacity of ketamine to enhance glutamate neurotransmission.